Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1007/bfb0053585
|View full text |Cite
|
Sign up to set email alerts
|

Specifying embedded systems with statecharts and Z: An agenda for cyclic software components

Abstract: Abstract. The application of formal techniques can contribute much to the quality of software, which is of utmost importance for safety-critical embedded systems. These techniques, however, are not easy to apply. In particular, methodological guidance is often unsatisfactory. We address this problem by the concept of an agenda. An agenda is a list of activities to be performed for solving a task in software engineering. Agendas used to support the application of formal specification techniques provide detailed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Grieskamp et al demonstrated the use of the agenda approach to support the systematic development of requirement specifications for a particular class of embedded safetycritical systems [25]. An agenda is a list of steps to be accomplished when carrying out some task in the context of software engineering.…”
Section: Related Workmentioning
confidence: 99%
“…Grieskamp et al demonstrated the use of the agenda approach to support the systematic development of requirement specifications for a particular class of embedded safetycritical systems [25]. An agenda is a list of steps to be accomplished when carrying out some task in the context of software engineering.…”
Section: Related Workmentioning
confidence: 99%
“…Combining Statecharts and Z for the design of safety-critical control systems [75] (1996), Integrated Formal Methods [17] (1996), A combination of Object-Z and CSP [14] (1997), Specifying embedded systems with Statecharts and Z [19] (1998), An Operational Semantics for Timed RAISE, TRSL [18] (1999), Linking DC together with TRSL [30] (2000), Study of graphical and temporal specification techniques [49] (2003), Integration of Specification Techniques [48] (2003).…”
Section: Integrating Formal Techniquesmentioning
confidence: 99%
“…Many other references could be given to papers that seeks to provide answers to integration issues: [75,17,14,32,19,11,60,77]. …”
Section: Integrating Formal Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Zed notations were type checked with the ESZ type checker but the Statechart semantics were not fully formalized. In addition, we reviewed several other case studies that utilized Zed for concretely defining data while using Statecharts as a behavioral description and evaluation method [7][8][9].…”
Section: Related Workmentioning
confidence: 99%